Design and Analysis of Interior Permanent Magnet Motor With Magnetic Isolation and Heat Dissipation Integrated Auxiliary Slot - Jingfeng Mao; Jin Huang; Xinyu Xu; Junqiang Zheng; Xinxing Zhang (IEEE Access)
This paper presents a novel auxiliary slot interior permanent-magnet (IPM) motor. It not only plays the role of magnetic isolation and reduces the eddy-current (EC) loss, but also facilitates the ventilation and heat dissipation of the rotor. Initially, using a high-speed 6-slot and 4-pole IPM motor as an example, the structure characteristics of the auxiliary slot permanent-magnet (PM) motor with magnetic isolation and heat dissipation are explained. Subsequently, the finite-element method (FEM) is employed to conduct a multi-objective optimization design on the characteristic parameters of the auxiliary slot. Additionally, the electromagnetic performance of the 6-slot and 4-pole IPM motor is systematically analyzed and evaluated. Furthermore, the auxiliary slot structure was investigated to improve the efficiency of heat dissipation. The heat dissipation capacity of the auxiliary slot was further enhanced by analyzing various shapes of auxiliary slots. The results demonstrate that the proposed auxiliary slot structure can significantly reduce the EC loss and greatly improve the heat dissipation effect. Finally, the prototype is proofed by decreasing the volume, and the relevant experimental verification is carried out.